1996
DOI: 10.1111/j.1600-0528.1996.tb00828.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of reasons for extraction of permanent teeth in Singapore

Abstract: A survey was carried out to determine the reasons for tooth extractions of permanent teeth in Singapore. Data were obtained from 52 dentists practising general dentistry over a period of 12 months. At the end of the 12-month period, data were collected from 1276 patients, from whom a total 272 teeth were extracted. In this population group, the results showed that the percentage of teeth extracted due to periodontal reasons and caries were about the same, that is 35.8% and 35.4%, respectively. There was an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
95
9
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(123 citation statements)
references
References 16 publications
13
95
9
6
Order By: Relevance
“…11 In addition, while Ong et al showed that caries and periodontal disease were of equal importance, the majority of their sample was aged less than 40 years. 13 Thus, comparison of tooth extraction data between different countries is fraught with difficulty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition, while Ong et al showed that caries and periodontal disease were of equal importance, the majority of their sample was aged less than 40 years. 13 Thus, comparison of tooth extraction data between different countries is fraught with difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…1,[7][8][9][10][11][12][13][14][15] These variations, however, are at least partly attributable to methodological differences. This is illustrated by comparison of the two Canadian studies.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture as a sequela of caries has been shown to be one of the main reasons for permanent tooth extractions [19][20][21][22][23] . In the same connection, the number of tooth extractions can be reduced effectively by preventing fractures, especially vertical root fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, root fracture is one of the major causes leading to tooth extraction. Hence, it is highly desirable to prevent fractures or limit the fracture line to the suprabony area [19][20][21][22][23] . Some researchers have reported methods of reinforcing thin root canal dentin wall with resin composites [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…6 The two most common causes of tooth loss in Asian population are dental caries and periodontal disease. 7 Secondary reasons for tooth loss are restricted access to dental services, health systems, and lack of oral health care. 8 Rural India accounts for 83.3% of the total population of India which accounts for majority of the population.…”
Section: 5005/jp-journals-10015-1440mentioning
confidence: 99%